Trade dependence, liberalization, and exports diversification in developing countries - Patrick N. Osakwe; Amelia U. Santos-Paulino; Berna Dogan (Journal of African Trade, 2018)
This paper explores the relationship between trade, trade liberalization, and exports diversification in developing and Sub-Saharan African (SSA) countries. The non-parametric analyses indicate that developing countries that are more open to trade (based on trade intensity) tend to have more diversified exports structures than those that are classified as less open. However, for SSA countries the non-parametric test shows that countries that are more open to trade have less diversified exports structures. Regarding the parametric analysis, the findings provide further evidence that trade liberalization, in the form of lower tariffs, contributes to exports diversification in developing countries, and the results for the long term are even stronger for SSA countries. With regard to trade intensity, the parametric estimations also confirm the results that trade is associated with diversification in developing countries and in SSA countries in the short term; however, for SSA countries, it actually leads to concentration in the long term, consistent with the non-parametric results. The empirical analyses also show that human capital, GDP per capita and institutions, play important roles in exports diversification.
Keywords: C33; F63; O19; O55; 330; Exports diversification; Trade policy; Trade openness; Structural economic transformation; SSA